What Are the Factors That Enable Thread Lifting to Last Longer? - Hong, Gi-Woong; Hu, Hyewon; Park, Soo-Yeon; Wan, Jovian; Yi, Kyu-Ho (Cosmetics (Basel), 2024)
Thread-lifting traditionally addressed aging-related skin laxity by leveraging precise thread placement and traction. However, recent advancements, notably cog threads, expanded its application to younger patients seeking facial contour refinement. These newer threads effectively lift sagging areas and refine facial contours, broadening the procedure’s appeal. Challenges arise in selecting threads due to variable physician preferences and patient needs. Clear indications for thread efficacy are vital for credibility and tailored selection. Thread choice depends on tissue laxity, necessitating lighter threads for minimal laxity and stronger ones for significant sagging. However, no single thread universally suits all cases. Combining different threads is favored for optimal outcomes and minimizing side effects. Excessive traction post-procedure may lead to prolonged discomfort and skin irregularities. Post-procedural tension adjustments through massage remain debated, potentially conflicting with minimally invasive principles. Understanding thread characteristics guides tailored selection, considering patient conditions and procedural goals. This comprehensive understanding extends beyond specific products, aiming for optimal outcomes in thread-lifting procedures. Key factors influencing outcomes encompass thread materials, thickness, cog shapes, insertion depth, lifting vectors, and absorbable thread expiration dates.